The Association Between Smoking and Gut Microbiome in Bangladesh. Issue 8 (3rd December 2019) - Nolan-Kenney, Rachel; Wu, Fen; Hu, Jiyuan; Yang, Liying; Kelly, Dervla; Li, Huilin; Jasmine, Farzana; Kibriya, Muhammad G; Parvez, Faruque; Shaheen, Ishrat; Sarwar, Golam; Ahmed, Alauddin; et al.
Abstract: Introduction: Epidemiological studies that investigate alterations in the gut microbial composition associated with smoking are lacking. This study examined the composition of the gut microbiome in smokers compared with nonsmokers. Aims and Methods: Stool samples were collected in a cross-sectional study of 249 participants selected from the Health Effects of Arsenic Longitudinal Study in Bangladesh. Microbial DNA was extracted from the fecal samples and sequenced by 16S rRNA gene sequencing. The associations of smoking status and intensity of smoking with the relative abundance or the absence and presence of individual bacterial taxon from phylum to genus levels were examined. Results: The relative abundance of bacterial taxa along the Erysipelotrichi -to- Catenibacterium lineage was significantly higher in current smokers compared to never-smokers. The odds ratio comparing the mean relative abundance in current smokers with that in never-smokers was 1.91 (95% confidence interval = 1.36–2.69) for the genus Catenibacterium and 1.89 (95% confidence interval = 1.39–2.56) for the family Erysipelotrichaceae, the order Erysipelotrichale, and the class Erysipelotrichi (false discovery rate-adjusted p values = .0008–.01). A dose–response association was observed for each of these bacterial taxa. The presence of Alphaproteobacteria was significantly greater comparing current with never-smokers (odds ratio = 4.85, false discovery rate-adjusted p values = .04). Conclusions: Our data in a Bangladeshi population are consistent with evidence of an association between smoking status and dosage with change in the gut bacterial composition. Implications: This study for the first time examined the relationship between smoking and the gut microbiome composition. The data suggest that smoking status may play an important role in the composition of the gut microbiome, especially among individuals with higher levels of tobacco exposure.